Dictionary for a better world : poems, quotes, and anecdotes from A to Z - Latham, Irene; Waters, Charles, 1973- (Carolrhoda Books, 2020)
Alphabetically organized collection of poems with one-world titles that express themes of courage, kindness, curiosity, love, and tolerance, accompanied by short essays from the author expounding on the poem and prompts for the reader to take positive action. Includes a list poetry resources.